2012
DOI: 10.5194/hessd-9-3339-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of climate change on sediment yield in the Mekong River Basin: a case study of the Nam Ou Basin, Lao PDR

Abstract: This paper evaluates the impact of climate change on sediment yield in the Nam Ou Basin located in Northern Laos. The Soil and Water Assessment Tool (SWAT) is used to assess future changes in sediment flux attributable to climate change. Future precipitation and temperature series are constructed through a delta change approach. As per the results, in general, temperature as well as precipitation show increasing trends in both scenarios, A2 and B2. However, monthly precipitation shows both increasing and decre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…Predicting the impact of climate change on water resources, agriculture, and other sectors is difficult [37] and needs the use of possible scenario changes defined by the Intergovernmental Panel on Climate Change (IPCC) [38]. The Fifth Assessment Report (AR5) of the IPCC was published in 2014.…”
Section: Construction Of Climate Scenarios Description Of Climate Chamentioning
confidence: 99%
“…Predicting the impact of climate change on water resources, agriculture, and other sectors is difficult [37] and needs the use of possible scenario changes defined by the Intergovernmental Panel on Climate Change (IPCC) [38]. The Fifth Assessment Report (AR5) of the IPCC was published in 2014.…”
Section: Construction Of Climate Scenarios Description Of Climate Chamentioning
confidence: 99%
“…Many studies have shown that climate change could significantly affect soil erosion [7][8][9][10][11]. The most direct impact of climate change on soil erosion is the change in the erosive power of rainfall [9][10][11][12][13]. The contribution of water as an erosion agent can be represented by rainfall erosivity (R-factor).…”
Section: Introductionmentioning
confidence: 99%
“…Land-use management practices (e.g., urbanization, changes in land use, land management and agricultural practices), changes in water management practices (e.g., dam constructions or demolition, streamflow regulation, introduction of flood control mechanisms) and river sand mining are the most prominent human-induced drivers that affect fluvial sediment supply [7,12,13,15,18]. Owing to the aforementioned factors, human activities have simultaneously increased catchment sediment yield via accelerated soil erosion, yet, have also significantly reduced the amount of sediment received by the coasts due to retention within reservoirs [3,7,13,15,16,[20][21][22]]. …”
Section: Factors Affecting Fluvial Sediment Supply To Coastsmentioning
confidence: 99%
“…The combined effect of reduced rainfall and increased temperature results in water stresses to plants, resulting in diminished growths and, hence, amplified soil erosion that results in a larger sediment yield from catchments. Contrariwise, high rainfall and low temperatures facilitate favourable conditions for plant growth, and hence reduce soil erosion, which in turn diminishes the sediment yield from catchments [16]. Global-scale studies indicate that the rivers contemporary discharge less water to the oceans due to both increased water usage and diminished precipitation [7,15,[17][18][19], which, in turn, directly affects fluvial sediment supply to the coasts and oceans.…”
Section: Factors Affecting Fluvial Sediment Supply To Coastsmentioning
confidence: 99%
See 1 more Smart Citation